2010
DOI: 10.1007/s10212-010-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of violent and non-violent computer game content on memory performance in adolescents

Abstract: The present study focuses on the short-term effects of electronic entertainment media on memory and learning processes. It compares the effects of violent versus nonviolent computer game content in a condition of playing and in another condition of watching the same game. The participants consisted of 83 female and 94 male adolescents with a mean age of 17.6 years. The dependent variables are memory for previously learnt verbal and visual material, memory for media-related content and physiological measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In addition, depending on their ability to avoid illness and save lives, participants were exposed to between 37 and 42 news pictures (M ¼ 38.5) that included a variety of possible items to remember. The pictures used in the present study, originating from the International Affective Picture System (IAPS) developed by Lang, Bradley, and Cuthbert (2005), had a mean arousal level of 5.06 (SD ¼ 0.09) IAPS norms.…”
Section: Designmentioning
confidence: 99%
“…In addition, depending on their ability to avoid illness and save lives, participants were exposed to between 37 and 42 news pictures (M ¼ 38.5) that included a variety of possible items to remember. The pictures used in the present study, originating from the International Affective Picture System (IAPS) developed by Lang, Bradley, and Cuthbert (2005), had a mean arousal level of 5.06 (SD ¼ 0.09) IAPS norms.…”
Section: Designmentioning
confidence: 99%
“…Contrarily to these studies, some other authors refuted these results indicating the absence of a clear relationship between playing VG and addiction, and violent or aggressive behavior 17 , 18 . Some studies focused their attention to cognitive aspects, suggesting that prolonged exposure to VGs may have a detrimental impact on the attentional sphere 16 , 19 , 20 , with possibility to evolve to a clinically relevant attentional deficit 21 , with worsened scholastic performance 22 , 23 and memory deficiency 24 . In addition to these effects, a negative correlation between exposure to VGs and cognitive proactive control has also been reported 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite their prevalence, the consequences of video-gaming to adolescent functioning are relatively under-studied and extant findings are inconsistent. Some studies have associated video-gaming with worse academic performance (Rehbein, Psych, Kleimann, Mediasci, & M€ oßle, 2010), memory deficits (Maass, Kollh€ orster, Riediger, Macdonald, & Lohaus, 2011), symptoms of inattention and ADHD (Chan & Rabinowitz, 2006), poor mood and heightened aggression. Conversely, other studies have found either no effect of video-gaming on academic performance (Gentile, Lynch, Linder, & Walsh, 2004;Smyth, 2007), or even beneficial associations between video-gaming and academic performance (Skoric, Teo, & Neo, 2009), working memory (Colzato, Van Den Wildenberg, Zmigrod, & Hommel, 2013), visualespatial skills and attention (Ventura, Shute, & Zhao, 2013).…”
Section: Introductionmentioning
confidence: 99%